2018
DOI: 10.1002/ceat.201700539
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Electrochemical Sensors for Anaerobic Digestion Process Control – Performance of Electroactive Biofilms under Real Conditions

Abstract: The autonomous growth of Geobacter sp.‐dominated biofilms on electrodes and their sensitivity on volatile fatty acids (VFAs) allows their application as biosensor. In this study, the implementation of a microbial electrochemical sensor in the anaerobic digestion (AD) process is reported. The amperometric sensor signal follows the acetate concentration profile in the AD process. Yet, the sensor's stability is impaired by the process conditions. Therefore, potential biofilm inhibitors are individually examined, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…For instance, Kretzschmar et al reported a microbial electrochemical biosensor using Geobacter sp.-dominated biofilms on electrodes for the detection of volatile fatty acids [ 8 ]. Using this amperometry-based biosensor, the researchers followed the profiles of acetate concentrations in the anaerobic digestion (AD) course.…”
Section: Microbial Electrochemical Biosensing In High Salinementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kretzschmar et al reported a microbial electrochemical biosensor using Geobacter sp.-dominated biofilms on electrodes for the detection of volatile fatty acids [ 8 ]. Using this amperometry-based biosensor, the researchers followed the profiles of acetate concentrations in the anaerobic digestion (AD) course.…”
Section: Microbial Electrochemical Biosensing In High Salinementioning
confidence: 99%
“…Among the many types of microbial electrochemical systems, the technology used most often for biosensing is the microbial fuel cell since the substrate of the bacterial cells is commonly the driver of the current output. Therefore, the current output can be related to the substrate concentration in a variety of wastewaters providing a self-powered sensor [ 7 , 8 , 9 , 10 ]. The long-term stability stems from the ability of microorganisms to continually reproduce, allowing for a near-infinite bioelectrode where the biocatalysts are being regenerated [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of bio-sensors has mainly been demonstrated for synthetic wastewaters and/or wastewaters with low suspended solids, e.g., in the recirculation loop of an upflow anaerobic fixed-bed reactor (Liu et al 2011). The application of a biosensor with a Geobacter anodireducens dominated anode in an anaerobic digester treating a mixture of maize silage and cow manure allowed accurate VFA measurements (Kretzschmar et al 2018). However, longterm stability in CSTR digesters remains to be validated.…”
Section: Biosensors For Process Stability Monitoringmentioning
confidence: 99%
“…Interference can range from substrate competition with methanogens, for example, for acetate, over the use of available terminal electron acceptors (TEA) other than the anode, to toxicity of specific compounds, as shown, for example, for ammonium . Using TEA other than the anode enables survival of EAM outside of biofilms, likely with fewer constraints in terms of substrate availability or mass transfer. ,, Alternative TEA that occur in AD are manifold, including, for instance, humic substances, iron and sulfur minerals, or even other microorganisms like methanogenic archaea that enable direct interspecies electron transfer (DIET). Using DIET, some methanogenic archaea, for example, Methanosarcina barkeri or M. horonobensis, are able to accept electrons directly from Geobacter spp.…”
Section: Introductionmentioning
confidence: 99%